متطلبات ارساء الحوكمة في البنوك العمومية الجزائرية حالة بنك الجزائر - عبادي, رندة (University of eloued جامعة الوادي, 2014)
عنوان المذكرةِ موسومٌ بـ:"متطلبات إرساء الحوكمة في البنوك العمومية–دراسة حالة بنك الجزائر-" وإشكاليتُهُ الرئيسةُ التي أحاول الإجابةَ عنها تتمحورُ حولَ ما هي الآليات اللازمة لإرساء مبادئ الحوكمة في البنوك العمومية ؟ وقد جاءَ الموضوعُ في ثلاث فصول : خُصِّصَ أولُها في دور البنك المركزي في الإشراف و الرقابة على الجهاز المصرفي وجُعِلَ ثانيها حول الإطار العام لحوكمة البنوك، وعُنِيَ ثالثُها:متطلبات إرساء الحوكمة لبنك الجزائر في الجهاز المصرفي الجزائري. ومِنَ النتائجِ الأساسيةِ التي وصلَ إليها البحثُ في هذا الموضوعِ أنّ تطبيق الحوكمة في المنظومة المصرفية الجزائرية لا يزال في مرحلته الأولية, واقترحَ من خلال هذا البحث انه يجب على الجهات الإشرافية الاستفادة عن كون بنك الجزائر عضو في بنك التسويات الدولية والاحتكاك بخبراء لجنة بازل للرقابة المصرفية من أجل تفعيل دوره الرقابي والإشرافي,كما يجب الاستمرار في تفعيل الدور الرقابي الذي يمارسه في مجال التحقيق من التزام البنوك بالقواعد والممارسات الفضلى للحوكمة The title of the thesis is " The establishment of governance in the public banks: Bank of Algeria a case study". And the main problematic of the topic is centered on the following question: What are the necessary mechanisms to establish the principles of governance in the public banks? This study contains three chapters; the first one is focused on the role of the Central Bank in supervision and control of the banking system. In the second chapter, I discussed the general framework of bank governance. And In the third chapter, I identified the requirements of the application of governance the Bank of Algeria on the Algerian banking system. The main result of the study is that the application of governance in the Algerian banking system is still its early stages. So that the research recommended that government should benefit from the membership of Algeria in the bank for international settlements, and contacting the experts of Basel committee on banking supervision in order to activate the oversight and supervisory role. We should also continue to boost its oversight role in the investigation of the Bank's commitments of the best rules and practices of corporate governance.
ماستر بنوك
Keywords: حوكمة البنوك ،بنك الجزائر ،البنوك العمومية الجزائرية; Bank governance, Bank of Algeria, the Algerian public banks